TAXATION OF SMALL BUSINESS AND ENTREPRENEURSHIP ENTITIES: FOREIGN PRACTICES - Turanboyev Boburjon Qodirjon o‘g‘li (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
In the process of improving the taxation of small business and entrepreneurship entities, it is important to analytically study the practical experiences of foreign countries. By analyzing tax systems, incentives, and support measures aimed at promoting small businesses in developed countries, and by applying these practices, important insights can be gained. This study develops specific proposals and recommendations for improving the tax system based on international experience, which can contribute to further liberalization of the national economy and support small business development.